(untitled) (NTU Journal of Agriculture and Veterinary Science, 2024)
The current study aimed to determine the prevalence of Cryptosporidium sp, Eimeria sp., Entamoeba spp.and Giardia sp. A total of 200 pieces of five different species of fresh fish were sampled. The study was conducted from August 2023 -February 2024. Microscopic examination was done by stomach and intestine direct smears stained Lugal iodine and floatation technique. Results showed that fish were infected with Cryptosporidium sp. 26.5%, Eimeria spp. 26.5%, Entamoeba spp. 1 % and Giardia sp. 3.5% . with no significant differences between them. As for months of the study, there were no significant infection rates where the rates ranged between 34.28% and 14.28% at p ? 0.05. Microscopically, Cryptosporidium oocysts were spheroidal to ovoidal , 4.6 - 5.5 X 3.8 - 4.7µm while Eimeria oocysts were spherical to ovoid, 12-19 µm. The cysts of Entamoeba were spherical, 10 to 18 µm. while Giardia cysts were oval with four nuclei, 8-12 ?m in size. Intestinal protozoa recorded in fish species in the current study may be due to age factor and water contamination.